2023
DOI: 10.1186/s12903-023-02894-3
|View full text |Cite
|
Sign up to set email alerts
|

Can antioxidant treatment replace delay in bracket bonding? An in vitro study

Abstract: Background Deterioration in shear bond strength has been reported after immediate bracket bonding following hydrogen peroxide bleaching. This study compared the effectiveness of three antioxidant agents, namely, alpha-tocopherol, green tea extract, and sodium ascorbate, in reversing the bleaching effect and as possible alternatives to delayed bonding. Methods A total of 105 extracted human premolars were arbitrarily assigned to 7 groups (n = 15 eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Numerous in vitro studies concerning applying antioxidants to enhance SBS have been performed [ 20 , 22 25 ]. These studies included an additional etching procedure involving phosphoric acid, leading to an increase in the duration of the clinical procedure [ 20 , 22 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous in vitro studies concerning applying antioxidants to enhance SBS have been performed [ 20 , 22 25 ]. These studies included an additional etching procedure involving phosphoric acid, leading to an increase in the duration of the clinical procedure [ 20 , 22 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous in vitro studies concerning applying antioxidants to enhance SBS have been performed [ 20 , 22 25 ]. These studies included an additional etching procedure involving phosphoric acid, leading to an increase in the duration of the clinical procedure [ 20 , 22 , 24 , 25 ]. A previous study proposed a method to improve the clinical effectiveness, reduce working time, and address this concern by combining antioxidant and acid etching solutions [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…39 Another study found that a 15-min application of antioxidants was found to be adequate after three 15-min bleaching sessions, in line with our findings. 40 The gel form was used as the key advantage of gel over solution is better control because of the gel's increased viscosity and a delayed release of the SA, which ensures its effectiveness over time. 16,37 According to the scales used for measuring tooth sensitivity, The Numerical Rating Scale (NRS) is easy to record, reliable, valid, sensitive, and presents the greatest accuracy.…”
Section: Resultsmentioning
confidence: 99%